Hydrogeological characterisation of regional faults and dolerite dykes in the Precambrian Basement and Karoo Supergroup (Tete Province, Mozambique) - Dippenaar, Matthys Alois (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.